Pengaruh Budaya Organisasi Dan Gaya Kepemimpinan Transformasional Terhadap Kinerja Pegawai Bagian Humas dan Protokol Sekretariat Daerah Kabupaten Banyuasin - Zein Ghozali; Munyati; Maulana Ali; Hendra Musa (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2023)
This study aims to examine the Effect of Organizational Culture and Transformational Leadership Style on Employee Performance. by using 2 independent variables in the form of Organizational Culture and Transformational Leadership Style and Employee Performance as the dependent variable. the sample was tested as many as 27 employees of the Public Relations and Protocol Section of the Banyuasin District Secretariat. The test was carried out by using multiple linear regression analysis of the CSS for Windows version 17.0 program. based on the results of the study showed that simultaneous independent variables have a positive and significant effect on employee performance. Based on the partial test, the variables of Organizational Culture and Transformational Leadership Style have a positive and significant effect on Employee Performance.